2017
DOI: 10.1186/s12917-017-1020-9
|View full text |Cite
|
Sign up to set email alerts
|

Relation of antioxidant status at admission and disease severity and outcome in dogs naturally infected with Babesia canis canis

Abstract: BackgroundCanine babesiosis is caused by species of the Babesia genus and has become an emerging disease worldwide. To the authors’ knowledge there are no reports in which antioxidants have been analyzed in different presentations of canine babesiosis or in which the prognostic value of antioxidants has been studied. The aim of this study was to evaluate whether oxidative stress could be related to the severity and outcome of canine babesiosis. For this purpose a profile consisting of four antioxidant biomarke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
42
2
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 51 publications
(53 reference statements)
3
42
2
4
Order By: Relevance
“…Recently, Al-Hosary et al (13) reported a significant increase in serum TAC in ewes infected with ticks. These results agree with those reported earlier in sheep (38), and dogs infested by babesiosis (32). Furthermore, Ciftci et al (39) observed that TAC levels decreased in Babesia vogeli infested dogs, but these variations were not found as statistically significant (P>0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Al-Hosary et al (13) reported a significant increase in serum TAC in ewes infected with ticks. These results agree with those reported earlier in sheep (38), and dogs infested by babesiosis (32). Furthermore, Ciftci et al (39) observed that TAC levels decreased in Babesia vogeli infested dogs, but these variations were not found as statistically significant (P>0.05).…”
Section: Discussionsupporting
confidence: 92%
“…Our research confi rmed the presence of oxidative stress in dogs infected with B. canis by examining serum malondialdehyde (MDA), an end product of lipid peroxidation, and relationship between paraoxonase 1 activity and high-density lipoprotein concentration [143,144]. In addition to the above, our latest research confi rmed changes in biomarkers related to the antioxidant status of dogs naturally infected with B. canis [145].…”
Section: Clinical Signs and Clinicopathological Abnormalities Of Babementioning
confidence: 88%
“…Canine babesiosis may be represented clinically as uncomplicated cases as a result of the hemolytic action of the protozoan or complicated cases due to systemic inflammatory reaction and disturbance in many organs function [37][38][39][40]. Diseased dogs under the present study showed only uncomplicated form of the disease.…”
mentioning
confidence: 61%